Solve for: 5(x-1) <= 3(x+3)

Expression: $5\left( x-1 \right) \leq 3\left( x+3 \right)$

Distribute $5$ through the parentheses

$5x-5 \leq 3\left( x+3 \right)$

Distribute $3$ through the parentheses

$5x-5 \leq 3x+9$

Move the variable to the left-hand side and change its sign

$5x-5-3x \leq 9$

Move the constant to the right-hand side and change its sign

$5x-3x \leq 9+5$

Collect like terms

$2x \leq 9+5$

Add the numbers

$2x \leq 14$

Divide both sides of the inequality by $2$

$\begin{align*}&x \leq 7 \\&\begin{array} { l }x \in \left\langle-\infty, 7\right]\end{array}\end{align*}$